2011
DOI: 10.1159/000328318
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome of Migrant Women Delivering in a Public Institution in Northern Italy

Abstract: Background/Aim: European societies are facing a wave of incoming immigrants and the needs of a new multiethnic obstetrical population. It remains controversial whether native and immigrant women have equivalent pregnancy outcomes. Methods: Perinatal indicators of the obstetric outcome were monitored in all delivering women during a 5-year period in a large academic public general hospital. We compared rates of preterm deliveries, low birth weight, cesarean section during labor, perineal tears, and fetal acidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 36 publications
7
44
1
1
Order By: Relevance
“…US [37,57,81] and Southern European [25,26,88] studies were too heterogeneous to combine, but tended towards higher rates. Analysis by parity showed primiparous African women to be more likely to have a caesarean [OR=2.24 (95% CI=1.63, 3.08)] [31,33,46,64] than non-migrants see Figure 1; multiparous women were also at increased risk [OR=2.02 (95%CI=1.51, 2.71)] [31,46].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…US [37,57,81] and Southern European [25,26,88] studies were too heterogeneous to combine, but tended towards higher rates. Analysis by parity showed primiparous African women to be more likely to have a caesarean [OR=2.24 (95% CI=1.63, 3.08)] [31,33,46,64] than non-migrants see Figure 1; multiparous women were also at increased risk [OR=2.02 (95%CI=1.51, 2.71)] [31,46].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis by type of caesarean suggests an excess risk of emergency caesareans for Sub-Saharan African women (all estimates above 1), although results were heterogeneous [17,31,33,64,82,88,91,94]. Risks for elective caesareans varied by receiving-country; three studies in France [17,31,94], one in Italy [88] and another in Australia [91] showed higher risks of a planned caesarean, while two other studies, one in Canada [64] and the other in Norway [82], found African women to have the same and lower risk respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, our study describes the impact of maternal age on perinatal mortality in a typical central European region with different ethnic groups and varying socioeconomic standards. Zanconato et al [16] previously demonstrated the impact of socioeconomic factors and ethnicity on the pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%